Synthesis of bisindolylmethanes and their cytotoxicity properties. - Mohan Naidu, Kalla Reddi; Khalivulla, Shaik Ibrahim; Syed Rasheed,; Fakurazi, Sharida; Arulselvan, Palanisamy; Lasekan, Olasegun; Abas, Faridah (MDPI Publishing, 2013)
Polymer supported dichlorophosphate (PEG-OPOCl2) is an efficient green catalyst for the electrophilic substitution reaction of indole with aromatic aldehydes, in neat condition, to afford an excellent yield of bis(indolyl) methanes with short reaction time, at room temperature. The synthesized compounds and their anti-cancer activity are evaluated.